Differences in aromatase expression and steroid hormone concentrations in the reproductive tissues of male domestic turkeys (Meleagris gallopavo) with white and yellow semen. Issue 5 (3rd September 2018) - Pardyak, L.; Kaminska, A.; Brzoskwinia, M.; Hejmej, A.; Kotula-Balak, M.; Jankowski, J.; Ciereszko, A.; Bilinska, B.
ABSTRACT: 1. To show hormonal differences between male turkeys with yellow semen syndrome (YSS) and white, normal semen (WNS), the expression of aromatase, oestrogen receptor α (ERα), and oestrogen receptor β (ERβ) as well as testosterone and oestradiol concentrations in YSS and WNS testes, epididymis, and ductus deferens were examined. 2. To measure gene expression levels of aromatase and oestrogen receptors (ERs), three complementary techniques (real-time PCR, Western blot, and immunohistochemistry) were used, whereas steroid hormone levels were determined radio-immunologically. 3. Upregulation of aromatase and ERα mRNAs in YSS testes ( P < 0.05; P < 0.01), epididymis ( P < 0.001; P < 0.001), and ductus deferens ( P < 0.05; P < 0.01) compared to those of WNS tissues was detected. Significant increases in the levels of aromatase and ERα proteins were detected in YSS testes ( P < 0.001; P < 0.05), epididymis ( P < 0.001; P < 0.001), and ductus deferens ( P < 0.001; P < 0.05). The expression of ERβ mRNA and protein level was upregulated in the testes ( P < 0.05; P < 0.01) and epididymis ( P < 0.001; P < 0.01) but not in ductus deferens where it was downregulated ( P < 0.01; P < 0.01). Increased intensity of immunoreactive proteins in YSS versus WNS reproductive tissues corroborated gene expression results. 4. Testosterone concentration diminished in YSS epididymis ( P < 0.05) and ductus deferens ( P < 0.05), but not in the testes, remaining at high level ( P < 0.05) compared to WNS values. Concomitantly, increased oestradiol concentration was found in YSS testes ( P < 0.05) and epididymis ( P < 0.05) but decreased in the ductus deferens ( P < 0.05). 5. From the published literature, this study is the first to demonstrate the ability for androgen aromatisation in the turkey reproductive tissues and to show the cellular targets for locally produced oestrogens. The data suggested that the androgen/oestrogen ratio is a mechanistic basis for amplification of differences between turkeys with white and yellow semen and that these results can have a relevance in applied sciences to widen the knowledge on domestic bird reproduction.